River basin management, development planning, and opportunities for debate around limits to growth - Smith, Heather M.; Blackstock, Kirsty Louise; Wall, Gill; Jeffrey, Paul (Elsevier, 2014)
Some of the latest global paradigms in sustainable water governance revolve around ideas of promoting greater integration within policy implementation processes that impact on land and water. The EU Water Framework Directive (WFD), seen by many as a ‘Sustainability Directive’, reflects this trend, and places particular emphasis on building linkages between water management and land use planning. This paper presents the results of a research project that examined this integrative vision in a real world setting – the emerging relationship between the WFD’s river basin management planning (RBMP) framework and the development planning (DP) system in Scotland. The project’s approach draws from interpretive policy analysis, and the results are based on analyses of key policy documents, as well as in-depth interviews, primarily with land use planning staff from local authorities, as well as other relevant public agencies such as the Scottish Environment Protection Agency (SEPA). The results show how an overarching political objective of ‘increasing sustainable economic growth’ is significantly affecting stakeholders’ understandings of the RBMP-DP relationship, as well as their own roles and responsibilities within that relationship. This has created barriers to the deliberation and potential operationalisation of environmental limits to growth in the built environment, which may be skewing decision-making processes in a way that undermines the RBMP framework and its objectives of protecting and improving the water environment.
Keywords: River basin management planning; Development planning; Policy integration; Sustainable economic growth; Policy framing